SLOPE STABILITY ANALYSIS ON BANJARBARU AREA, PIT PUNAI, JOBSITE PT. PAMAPERSADA NUSANTARA DISTRICK ASMI IN KAPUAS, KALIMANTAN TENGAH - Ramadhani Karina, Baiq
PT. Pamapersada Nusantara is a coal mining contractor from PT. Asmin Bara Bronang. PT. Asmin Bara Bronang whom has mining business license area (WIUP) in Central Kalimantan. When mining operations end at the limit, landslide symptoms appear which cause mining operations to cease due to safety factors. In order for the mining sequence to continue running, analysis of slope stability is needed to provide recommendations that are safe in terms of safety factors and failure probability. Slope stability analysis is used, by comparing the processing results of Slide 6.0 software with the Minister of Energy and Mineral Resources Decree No. 1827 K / 30 / MEM / 2018. The slide probability analysis is carried out by collecting laboratory test data in the form of content weight, cohesion and internal friction angle which have been sorted from the smallest to the largest value. Then performed a goodness of fit test to select the best distribution function using the Kolmogorov-Smirnov method followed by the Akaike Information Criterion. The output is the average value, standard deviation, relative maximum, and relative minimum which will be input parameters for the Monte-Carlo simulation method using Slide 6.0 software. The results of the analysis of the existing conditions with a dynamic load of 0.08g and a pore water factor (hu): 0.6 & 1 resulted in FK = 0.7 - 1 and PK = 39.2 - 100%. For LOM design with dynamic load and Hu of 1 & 0.6 yields FK = 0.5 - 0.8 and PK = 100%. For recommendation 1 with dynamic load and Hu 1 yields FK = 1 and PK = 75% for the arc slip plane; FK = 1,1 and PK = 16,6% for the combined fault and BLLA slip plane; FK = 5,6 and PK = 0% for the combined fault and carbonaceous clay slip plane. For recommendation 2 applying dynamic load with Hu 1 & 0.6 yields FK = 1.3 - 5.4 and PK = 0%. According to the Minister of Energy and Mineral Resources No. 1827 K / 30 / MEM / 2018 the results of the probability analysis that have FK ? 1.1 and the value of the sliding probability ? 5% are declared safe for the overall slope type with high landslide severity. So it can be said that the slope is in safe condition by doing the flow and installing the counterweight.